Suicidal bupropion ingestions in adolescents: increased morbidity compared with other antidepressants. (4th May 2018) - Sheridan, David C.; Lin, Amber; Zane Horowitz, B.
Abstract: Objective: Bupropion is often categorized as a newer generation antidepressant and assessed with serotonin reuptake inhibitors as a lower risk than older tricyclic antidepressants (TCAs). The objective of this study was to compare outcomes in adolescent suicide from ingestions between bupropion and TCA medications. Study design: An analysis of the National Poison Data System for exposures coded "suspected suicide" in adolescents (age: 13–19) was undertaken for the years 2013–2016 and included TCAs or bupropion. We compared clinical effects, therapies and medical outcomes. Results: Over the four-year period there were 2253 bupropion and 1496 TCA adolescent suspected suicide calls. There was a significant linear increase in bupropion ingestions over the four years. Across all years, there were on average 189.2 (95% CI: 58.1–320.4; p  = .01) more ingestions of bupropion than TCA. When comparing bupropion to a TCA, ingestions of bupropion were significantly more likely to be accompanied by seizure (30.7% vs 3.9%; p  < .01), to be admitted (74.8% vs 61.6%; p  < .01) and medical outcomes to be coded as a major outcome (19.3% vs 10.0%; p  < .01). The number of cases with death or major clinical outcome for both increased over the four-year period. Ingestions of bupropion were less likely to have hypotension (2.7% vs 8.0%; p  < .01) and less likely to be intubated (5.6% vs 16.4%; p  < .01) as compared to ingestions of TCA. Conclusions: Adolescents who overdose on a single medication in a suicide attempt with bupropion have a statistically significant higher incidence of major outcomes and seizures. The risks of bupropion as a potential means of suicidal gesture by overdose must be considered, and weighed against its benefits and side effect profile when choosing an appropriate agent for the treatment of depression in adolescents.